Analisis Kapabilitas Pemasaran Dan Orientasi Pasar Terhadap Keunggulan Daya Saing UMKM Seketeng - Rahayu, Sri; Diatmika, I Putu Gede (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Marketing capability as the ability to use inputs and resources, such as financial resources and existing customer bases to be used more efficiently in generating desired sales. Micro, Small and Medium Enterprises that are market-oriented and have marketing capabilities are needed to achieve marketing performance and competitive advantage. The purpose of this study was to analyze marketing capabilities, market orientation towards the competitive advantage of Micro, Small and Medium Enterprises in Seketeng Village, Sumbawa Regency. The research method uses a quantitative descriptive approach. The data analysis technique in this study uses the Statistical Package for the Social Sciences analysis. The results of the study indicate that Marketing Capability and Market Orientation simultaneously or together have a significant influence on the Competitive Advantage of Micro, Small and Medium Enterprises in Seketeng Village with a significance level of 5% (0.05) and F = (k; n-k) = f (2; 68) = 3.13. So that the Ftable value is obtained of 3.13 because the Fcount value> Ftable (24,915> 3.13). To improve the productivity of MSMEs in Seketeng Village, Sumbawa Regency, it is important to highlight the ability of marketing capabilities and market orientation in improving MSME marketing performance. MSMEs that have better marketing capabilities and use digital channels to promote their products or services tend to perform better in terms of sales growth, customer acquisition, customer retention and customer satisfaction. In addition, marketing capabilities play an important role in improving the competitive advantage of MSMEs. MSMEs need marketing capabilities to build sustainable competitive advantages because marketing capabilities create valuable intangible assets, such as rare and difficult-to-imitate knowledge.